Are upper urinary tract stones more common in more deprived populations?. (May 2020) - Radcliffe, Robert S; Miller, Steven; Williams, Simon T; Stanford, Richard FJ
Purpose: To examine the relationship between deprivation and upper tract calculus formation, and provide a contemporary estimate of the incidence of upper urinary tract stone disease. Methods: A retrospective review of hospital episodes for patients presenting to our institution with upper urinary tract stone disease in a 3-year period between 2010 and 2014. Incidence of stone disease was calculated and stratified according to deprivation, as measured by the index of multiple deprivation (IMD) and its subdomains. Poisson regression was used to model the relationship between deprivation and stone disease. Results: The overall incidence of upper urinary tract stone disease was 115 patients/100, 000 person-years (95% confidence interval (CI) 108–122 per 100, 000 person-years). There is a link between the IMD (as well as a number of its subdomains) and stone disease. The rate of incident stone disease was 50.6% higher in the most deprived quintile of the IMD when compared to the least deprived ( p < 0.001). Multivariate Poisson regression found that education, skills and training deprivation was the subdomain that predicted stone disease most strongly, with the incidence rate ratio being 1.15 (95% CI 1.053–1.261) for each increase in quintile. Conclusion: This study provides a contemporary measure of the incidence of upper urinary tract stone disease derived from a population in the Midlands of England. It informs our understanding of the link between types of deprivation and stone occurrence. Level of evidence: 2b